UMP appointed accredited Bosch Rexroth Academy training centre - Mimi Rabita, Abdul Wahit (2023)
GERMANY, 17 April 2023 - Universiti Malaysia Pahang (UMP) received the accreditation of UMP Bosch Rexroth Academy as a training centre for the IR4.0 Industrial Automation and Control & Drive certification programmes.